Lessons Learned Using Theory of Mind Methods to Investigate User Social Awareness in Virtual Role-Play - Hall, Lynne; Woods, Sarah; Hall, Marc (Human Technology, 2009)
Theory of mind (ToM) methods were used to investigate children's interpretations of the social and emotional states of synthetic pedagogical characters, focusing on children's cognitive and affective empathic responses to characters in bullying scenarios and their social awareness and understanding of the characters' situations. Although cognitive approaches typically do not consider user social awareness and emotional understanding and their roles in interaction, this is critical for our research on empathic engagement. We present a novel approach focusing on story and character comprehension using concepts from ToM methods to understand children's interpretations of characters within virtual role play scenarios and compare these with an adult perspective. Our results identify that ToM methods offer considerable potential for determining user social awareness and emotional understanding, particularly highlighting that adults and children have different perspectives on how victims and bullies feel.